The Plebs : organ of the National Council of Labour Colleges. - National Council of Labour Colleges (NCLC) (London : NCLC Publishing Society, 1930)
Bibliotheek Camille Huysmans
Periodiciteit: maandelijks
Engels
Periodiek
Keywords: arbeidersopvoeding